Amazonia. Entre la integración regional y la globalización (2015)
La Amazonia es diversa, heterogénea y compleja por excelencia; es multidimensional pero integral, desde los aspectos biofísicos, socioeconómicos, sociopolíticos y socioculturales. De ahí que existan varias Amazonias con diversos tipos de conflictos, tanto por la apropiación del territorio como del patrimonio natural que ella alberga. Este documento pretende mostrar las diferentes categorías sobre la Amazonia. Posteriormente se describe cómo la Amazonía está en la mira de la globalización neoliberal y cómo se viene insertado en los flujos comerciales dentro de un marco geopolítico en la conformación de un Espacio Común Sudamericano como es la Comunidad Sudamericana de Naciones (CASA) a partir de la integración regional de Mercado Común del Sur (MERCOSUR) más Chile, Guyana, Surinam, la Comunidad Andina (CAN) y como observador Panamá.ABSTRACTAmazonian region is diverse, heterogeneous and complex by excellence; is multidimensional but integral, since such things as biophysics aspects, until socioeconomics, sociopolitical and sociocultural ones. That is why different regions of Amazonian coexist with different conflicts dealing with territory appropriation as well as natural patrimony which is inherent to the region.This document pretends to show the different categories about Amazonian region. After that it is described how Amazonian region is in the target of neoliberal globalization and how it is coming inserted by commercial flows ina geopolitical situation that has to be with conformation of a South American common space as the South American community of nations (SACN) since the regional common market integration of the south (MERCOSUR) plus Chile, Guyana, Surinam, Andean Community and Panama as watcher.